Application of the Collaborative Problem Solving Method by Using Big Data Analytics Technology in Entrepreneurship Learning to Improve Students' Complex Thinking Skills in Indonesia - Sumarno, Sumarno (Universitas Negeri Makassar, 2023)
This qualitative research study provides evidence that combining the collaborative problem-solving method with big data analytics technology is an effective approach to enhancing students' complex thinking skills in entrepreneurship learning. The research used a case study design to investigate the impact of the method on 30 students in an entrepreneurship course. The study has implications for educators and instructional designers seeking to improve students' critical thinking, creativity, collaboration, and data analysis skills in entrepreneurship education. The study highlights the importance of collaborative problem-solving and technology in entrepreneurship education. Future research is needed to investigate the long-term impact of the method on students' learning outcomes and its generalizability to other domains.